Management of anal cancer patients – a pattern of care analysis in German-speaking countries - Martin, Daniel (Radiat Oncol, 2020)
BACKGROUND: Radiotherapy dose and target volume prescriptions for anal squamous cell carcinoma (ASCC) vary considerably in daily practice and guidelines, including those from NCCN, UK, Australasian, and ESMO. We conducted a pattern-of-care survey to assess the patient management in German speaking countries. METHODS: We developed an anonymous questionnaire comprising 18 questions on diagnosis and treatment of ASCC. The survey was sent to 361 DEGRO-associated institutions, including 41 university hospitals, 118 non-university institutions, and 202 private practices. RESULTS: We received a total of 101 (28%) surveys, including 20 (19.8%) from university, 36 (35.6%) from non-university clinics, and 45 (44.6%) from private practices. A total of 28 (27.8%) institutions reported to treat more than 5 patients with early-stage ASCC and 42 (41.6%) institutions treat more than 5 patients with locoregionally-advanced ASCC per year. Biopsy of suspicious inguinal nodes was advocated in only 12 (11.8%) centers. Screening for human immunodeficiency virus (HIV) is done in 28 (27.7%). Intensity modulated radiotherapy or similar techniques are used in 97%. The elective lymph node dose ranged from 30.6 Gy to 52.8 Gy, whereas 87% prescribed 50.4–55. 8 Gy (range: 30.6 to 59.4 Gy) to the involved lymph nodes. The dose to gross disease of cT1 or cT2 ASCC ranged from 50 to ≥60 Gy. For cT3 or cT4 tumors the target dose ranged from 54 Gy to more than 60 Gy, with 76 (75.2%) institutions prescribing 59.4 Gy. The preferred concurrent chemotherapy regimen was 5-FU/Mitomycin C, whereas 6 (6%) prescribed Capecitabine/Mitomycin C. HIV-positive patients are treated with full-dose CRT in 87 (86.1%) institutions. First assessment for clinical response is reported to be performed at 4–6 weeks after completion of CRT in 2 (2%) institutions, at 6–8 weeks in 20 (19.8%), and 79 (78%) institutions wait up to 5 months. CONCLUSIONS: We observed marked differences in radiotherapy doses and treatment technique in patients with ASCC, and also variable approaches for patients with HIV. These data underline the need for an consensus treatment guideline for ASCC.